TRAINING TIPS FOR SUCCESSFUL HUMAN RESOURCES MANAGEMENT AND CHARACTERISTICS FOR POSTGRADUATE STUDENTS OF IBNU SINA UNIVERSITY - Sudianto Sudianto; Mulyadi Mulyadi; Sabri Sabri; Andi Hidayatul Fadlilah; Sumardin Sumardin; Hendri Herman (International Journal of Engagement and Empowerment, 2022)
Human resource development is an activity carried out so that their knowledge, abilities, and skills guides by their work. With this development activity, it hopes that it can improve and overcome shortcomings in carrying out work better. With the development of science and technologyStudents who have graduated are expected to become excellent and moral individuals. Constantly experience rapid development and be based on a noble moral foundation. As we now see, the business slogan of a state-owned entity wants the existing human resources to all expect to be "berakhlak" to provide the best service. (Siddiq) because honesty is expensive. In this day and age, Parents can teach untouched nature by getting children used to being honest in words and deeds. Trust (Amanah) also has an expensive value. Trust can lose with betrayal. The second trait position the father and mother of the government have done as well as possible. To be able to be an example for subordinates. Third Tabligh (Conveying) Conveying a good is easy for someone